ANALISIS TOKOH NEHEMIA SEBAGAI REFLEKSI PROFESIONALITAS PEMIMPIN GEREJAWI - Priyono, Joko (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This research analyzes the figure of Nehemiah as a reflection of the professionalism of ecclesiastical leaders, with the aim of identifying leadership principles relevant to the contemporary church. Using the Bible Character Study method, this study conducts an in-depth analysis of Nehemiah through narrative examination, historical context, and his main characteristics. The findings indicate that Nehemiah is a model of professional leadership characterized by integrity, diplomatic skills, meticulous planning, effective crisis management, commitment to social justice, dedication to his duties, and servant leadership. Additionally, Nehemiah emphasizes the importance of spiritual and moral renewal in leadership. This study concludes that Nehemiah's leadership principles are highly relevant and applicable to modern ecclesiastical leadership. By emulating Nehemiah's characteristics and actions, church leaders can develop leadership that is effective, integrous, and positively impactful for the church community.